Selected decisions of the International Monetary Fund and selected documents : 8th issue IMF - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1978)
The book is general application and relate to obligations, policies, or procedures under the articles of agreement. Decisions of the fund that are included in the bye laws and the rules and regulations.
Some issues have accompanying annex volumes.
aia 05/02/2019
Loans
Keywords: International finance; Resolutions of IMF; Internationale financiën.; Decisions of IMF